A systematic review and quality assessment of complementary and alternative medicine recommendations in insomnia clinical practice guidelines - Jeremy Y. Ng; Nandana D. Parakh (BMC, 2021)
Abstract Background Sleep disorders encompass a wide range of conditions which affect the quality and quantity of sleep, with insomnia being a specific type of sleep disorder of focus in this review. Complementary and alternative medicine (CAM) is often utilized for various sleep disorders. Approximately 4.5% of individuals diagnosed with insomnia in the United States have used a CAM therapy to treat their condition. This systematic review identifies the quantity and assesses the quality of clinical practice guidelines (CPGs) which contain CAM recommendations for insomnia. Methods MEDLINE, EMBASE and CINAHL were systematically searched from 2009 to 2020, along with the Guidelines International Network, the National Center for Complementary and Integrative Health website, the National Institute for Health and Care Excellence, and the Emergency Care Research Institute. CPGs which focused on the treatment and/or management of insomnia in adults were assessed with the Appraisal of Guidelines, Research and Evaluation II (AGREE II) instrument. Results From 277 total results, 250 results were unique, 9 CPGs mentioned CAM for insomnia, and 6 out of the 9 made CAM recommendations relevant to insomnia. Scaled domain percentages from highest to lowest were scope and purpose, clarity of presentation, editorial independence, stakeholder involvement, rigour of development, and applicability. Quality varied within and across CPGs. Conclusions The CPGs which contained CAM recommendations for insomnia and which scored well could be used by health care professionals and patients to discuss the use of CAM therapies for the treatment/management of insomnia, while CPGs which scored lower could be improved in future updates according to AGREE II.